THE INFLUENCE OF PROFITABILITY, LEVERAGE, AND FIRM SIZE ON FIRM VALUE OF THE BANKING SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE - Christian Febianto; Merry Susanti (International Journal of Application on Economics and Business, 2024)
This research was conducted to empirically test the effect of profitability (ROA), leverage (DAR), and firm size as independent variables on firm value (PBV) as the dependent variable in banking sector companies listed on the IDX in the 2018–2021 period. The technique used in selecting samples in this research was purposive sampling, with a total sample size of 30 companies. The number of observations in this research was 120, with a sample of 30 companies per year for four years. The data in this research was also managed using Microsoft Excell 2021, and data processing was done using IBM SPSS version 25 software. The results show that profitability (ROA) has a positive and significant effect on firm value, leverage (DAR) has a positive and significant effect on firm value, and firm size also has a positive and significant effect on company value.